(untitled) (CIPEEX, 2024)
This research seeks to carry out a study on Trade Union Law, based on the constitutional idea of ​​freedom in Brazil. The constitutionalization of the principle of union unity will be analyzed in light of the Brazilian Constitutional Charters, whose origins come from the Polish Constitution (1937). The study aims to analyze and understand whether the constitutional status of the principle of unity can be an impediment to the advancement of freedom of association. Unicity is provided for in article 8 of CF/88, a provision that conveys topics considered to be essential constitutional clauses. Article 60, § 4, of CF/88 discusses the impossibility of abolishing individual freedoms. It turns out that the principle of union unity restricts the existence of a single union to represent the category on a given territorial basis. Therefore, the work presents the following problem: when dealing with the principle of union unity, is there a possibility that this principle is restricting individual freedoms or union freedom? Thus, the study proposes to answer the problem and several questions, with the aim of a substantial transformation in society. It is worth highlighting that the work was based on bibliographical research, following the deductive method, seeking a coherent legal construction regarding Trade Union Law and analysis of the principle of uniqueness. It was concluded that constitutionalization of Trade Union Law norms is not harmful. The problem consists of constitutional restrictions on Trade Union Rights, as in the case of union unity, which, mainly due to the qualified quorum for constitutional amendments, are difficult to be revoked, not to mention the lack of political will to do so.